Determining Factors of Flora and Fauna Diversity Change in Khilau Sub-Sub, Bulog Sub-DAS, Sekampung Watershed - Darma, Hafid Azi; Bintoro, Afif; Duryat, Duryat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
Natural resources utilized in unsustainably management, lead to the extinction of biodiversity. The objectives of the research was to figure out the factors related to human activity in natural resources management at sub-sub watershed of khilau influenced to the change of biodiversity in the area. An historical analysis continued with the agrarian diagnosis was emploed as the research method. The result of the study showed that there ware four factors influenced to the biodiversity in sub sub watershed of khilau such as economic factor which is the increasing of commodities price; politic factor which is the occur of reformation lead to forest land occupation by the people; social factor which is the change of agricultur practice from subsistence to commercial products; and cultural factor which is influenced of ethnic in natural resources management. Before the exsisting of community, the area was covered by virgin forest with more than 32 species of flora and 25 species of fauna with the domination of endemic species, the exsistance of human activities lead to increasing of flora to 33 species with the dominance of commercial plants, but in other hand dicreasing fauna to 8 species. Key words: biodiversity, Bulog Watershed, flora and fauna, Khilau Watershed